Problematika Penerapan Model Problem Based Learning Pada Pelajaran PAI di SMAN 3 Palangka Raya - Prayetno, Riscky Edy; Mazrur, Mazrur; Hikmah, Nurul (Jayapangus Press, 2025)
This study identifies and analyzes the problems of implementing the Problem Based Learning (PBL) model in Islamic Religious Education (PAI) learning at SMAN 3 Palangka Raya. The background of this study is based on the importance of learning innovation in improving the quality of the learning process, especially in PAI subjects which play an important role in the formation of character and morals of students. However, the implementation of the PBL model in schools still encounters various obstacles from various aspects. This study uses a descriptive qualitative approach with a case study method. Data were collected through interviews, observations, and documentation of PAI teachers, student affairs vice principals, and grade XI students. The results of the study indicate that the problems of PBL implementation include three main aspects, namely (1) teacher aspects, which include limited understanding of the syntax of PBL implementation, difficulties in compiling teaching modules, and limited training, (2) student aspects, such as low interest, unfamiliarity with the PBL approach and weak group cooperation, and (3) environmental aspects, such as limited facilities, minimal learning time, and diverse cultural backgrounds of students. The most dominant obstacle lies in teachers' lack of preparedness in systematically designing PBL scenarios, followed by low student participation in group discussions. This study confirms that successful PBL implementation requires improved teacher competency through regular training, more adequate infrastructure support, and strategies to strengthen student motivation for active participation. Other recommendations include increasing the time allocated for Islamic Religious Education (PAI) and utilizing technology-based learning media to support the effectiveness of problem-based discussions. By meeting these factors, PBL has the potential to create more effective, applicable, and meaningful Islamic Religious Education (PAI) learning.